Novel concept for the epaxial/hypaxial boundary based on neuronal development. Issue 3 (12th August 2020) - Nagashima, Hiroshi; Koga, Daisuke; Kusumi, Satoshi; Mukaigasa, Katsuki; Yaginuma, Hiroyuki; Ushiki, Tatsuo; Sato, Noboru
Abstract: Trunk muscles in vertebrates are classified as either dorsal epaxial or ventral hypaxial muscles. Epaxial and hypaxial muscles are defined as muscles innervated by the dorsal and ventral rami of spinal nerves, respectively. Each cluster of spinal motor neurons passing through dorsal rami innervates epaxial muscles, whereas clusters traveling on the ventral rami innervate hypaxial muscles. Herein, we show that some motor neurons exhibiting molecular profiles for epaxial muscles follow a path in the ventral rami. Dorsal deep‐shoulder muscles and some body wall muscles are defined as hypaxial due to innervation via the ventral rami, but a part of these ventral rami has the molecular profile of motor neurons that innervate epaxial muscles. Thus, the epaxial and hypaxial boundary cannot be determined simply by the ramification pattern of spinal nerves. We propose that, although muscle innervation occurs via the ventral rami, dorsal deep‐shoulder muscles and some body wall muscles represent an intermediate group that lies between epaxial and hypaxial muscles. Abstract : Although epaxial and hypaxial muscles in vertebrates are innervated by MMC and HMC neurons, respectively, some muscles have been found to receive dual innervation from both MMC and HMC. These muscles are situated between the epaxial and hypaxial muscles, and the term 'midaxial muscles' has been coined to refer to these transitional muscles.